Rekontruksi Toleransi Moderasi Beragama Melalui Penguatan Kearifan Lokal di Desa Kuripan Utara Kecamatan Kuripan - I Wayan Wirata (Jurnal Penelitian Agama Hindu, 2022)
Cultural diversity in Kuripan Village is believed to be a destiny that should not be asked for, but a gift from Ida Sang Hyang Widhi Wasa. In improving the quality of religious life, religious people in West Lombok Regency always take a social-religious approach by referring to the gugon tuwon concept which is guided by regional culture and religious literature. The implementation of traditional ceremonies indicates that there is awareness of the importance of local culture in every implementation of religious ceremonies. By implementing local culture, one form of embodiment of the three foundations of Hinduism is through literature (tattwa), morals (susila), and ceremonies (upacara). Thus, a devotional path is needed that brings the Kuripan community to self-improvement both materially and spiritually. In addition, when the Maulud Prophet SAW ceremony, the Hindus help cook, welcome guests, and at the same time attend the invitation together. The existence of a sense of togetherness and brotherhood has implications for communication between citizens that is conducive and mutual respect and understanding of the importance of local customs and culture. In this study using qualitative research by answering questions by examining various activities and social interactions of people in a place and individuals who live in that place (Berg, 2001). The data collection techniques used in this study are: 1) Observation by involving researchers in the daily activities of the object under study, besides that the researcher can observe the object of research in a comprehensive manner; 2). Interviews with the aim of gathering information about the construction of religious moderation tolerance; and 3) Documentation is used in this research to find documents related to research on the construction of religious moderation in Kuripan Utara Village. The results of research on the construction of religious tolerance are friendly/simakrama, mutual assistance and mutual cooperation, the implementation of religious ceremonies, and the assistance of religious institutions. While the factors include history, humanity, religion, culture, and education and their implications through togetherness towards kinship, peace, and unity.